Efektivitas Komunikasi Interpersonal Pustakawan dalam Layanan Sirkulasi di Dinas Perpustakaan dan Kearsipan Provinsi Lampung - Mustofa, Muhamad Bisri; Ulvi, Sahelga; Wuryan, Siti (Universitas Teuku Umar, 2024)
The study aims to identify The effectiveness of Librarians' interpersonal communication within circulation services at the Library and Archives Division of Lampung Province, as well as to comprehend the nature of the circulation services offered within the organization. The employed research approach with descriptive qualitative methodology, that describes information about the problem under study. Methods of gathering information encompassed observing, conducting interviews, and utilizing documentation. Data was subsequently analyzed by condensing, presenting, and drawing conclusions. The findings indicate that interpersonal communication holds significance in delivering library services, encompassing abilities like openness, empathy, support, positive attitude, and equality. Researchers interviewed 5 librarians and 5 users, using a structured interview approach. These results indicate that librarians have implemented various communication skills, including openness, empathy, support, positive attitude, and equal treatment. Even so, the views of the users are different, they argue that the application of these skills is still not optimal. In conclusion, overall, circulation services provided by librarians at the Library and Archives Division of Lampung Province, are considered quite good, but the opinions of users indicate that the implementation of communication skills still needs to be improved.